Pengembangan Video Pembelajaran Al-Qur’an Hadis Pada Materi Makanan Yang Halal Dan Baik Di MAN 2 Kota Padang Panjang - Nabjema Iqnesdha Syahwir Papude; Supriadi Supriadi; Supratman Zakir; Darul Ilmi (KOLONI, 2022)
The background of the problem in this research is the process of learning and teaching at MAN 2 Padang Panjang City on the subjects of Al-Qur'an Hadith still tends to use the lecture method. In the teaching and learning process, students often only listen and take notes on the material presented by the teacher, resulting in students being less active and involved in the teaching and learning process. To overcome this problem, the researcher developed a video media for learning Al-Qur'an Hadith on halal and good food materials in Al-Qur'an Hadith subjects. The purpose of this research is to develop valid, practical and effective video-based learning media. The research method used in this study is the Research And Development (R&D) method using the 4D version approach, namely Define, Design, Develop and Disseminate. The product test used in this study is the validity test, namely content, construct and language using the Aiken's V formula. The practicality test by the Al-Qur'an Hadith teacher using the Moment Kappa formula and the effectiveness test by students using the N-Gain formula. The results of the study indicate that the learning media of the Qur'an Hadith on halal and good food materials can be used by teachers and students of class XI IPA 2 at MAN 2 Padang Panjang City. For product validity test of 0.87 which is declared valid, product practicality test results of 0.95 which are declared very practical and for product effectiveness test results of 0.82 which are stated to be very effective. So it can be concluded that the learning media of the Qur'an Hadith on halal and good food materials as learning media is valid, practical and effective. Keywords: Video Development, Learning Video, Learning